Obesity-Associated Metabolic Disturbances Reverse the Antioxidant and Anti-Inflammatory Properties of High-Density Lipoproteins in Microglial Cells - Elena Grao-Cruces (MDPI AG, 2021)
High-density lipoproteins (HDLs) play an important role in reverse cholesterol transport and present antioxidant properties, among others. In the central nervous system (CNS), there are HDLs, where these lipoproteins could influence brain health. Owing to the new evidence of HDL functionality remodeling in obese patients, and the fact that obesity-associated metabolic disturbances is pro-inflammatory and pro-oxidant, the aim of this study was to investigate if HDL functions are depleted in obese patients and obesity-associated microenvironment. HDLs were isolated from normal-weight healthy (nwHDL) and obese men (obHDL). The oxHDL level was measured by malondialdehyde and 4-hydroxynoneal peroxided products. BV2 microglial cells were exposed to different concentrations of nwHDL and obHDL in different obesity-associated pro-inflammatory microenvironments. Our results showed that hyperleptinemia increased oxHDL levels. In addition, nwHDLs reduced pro-inflammatory cytokines’ release and M1 marker gene expression in BV2 microglial cells. Nevertheless, both nwHDL co-administered with LPS+leptin and obHDL promoted BV2 microglial activation and a higher pro-inflammatory cytokine production, thus confirming that obesity-associated metabolic disturbances reverse the antioxidant and anti-inflammatory properties of HDLs in microglial cells.